(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
RÉSUMÉ: La Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) compte, depuis ce début de 21eme siècle, parmi les organisations de garantie des droits de l’homme, avec la révision du mandat de sa Cour de justice en 2005. Depuis, cette Cour officie dans le domaine des droits de l’homme, avec audace et volontarisme. Toutefois, l’exercice de ce mandat suscite quelques interrogations, relativement notamment à sa légalité et à son opportunité. En se penchant sur certaines de ces questions, la présente étude révèle qu’en dépit du silence des textes, le lien intrinsèque entre les droits de l’homme et la réalisation de son objet, légitime la revendication par l’organisation d’une compétence pour les protéger. Quant au dispositif - atypique – qui, en l’absence d’un catalogue propre, repose sur des normes exogènes que s’approprie l’organisation, il ne souffre d’aucune irrégularité. Des ressources du droit international, en général, et du droit de la CEDEAO, en particulier, soutiennent sa régularité, même si le régime des règles ainsi importées demeure indécis. Outre cette légalité établie, le mécanisme de la CEDEAO peut se prévaloir d’une certaine efficacité, en raison de la nature communautaire du système d’ancrage et de la juridiction immédiate qu’a revendiquée la Cour sur les cas de violations des droits de l’homme. TITLE AND ABSTRACT IN ENGLISH: The ECOWAS human rights protection mechanism amid borrowing and appropriation of the instruments of the continental system ABSTRACT: Since the beginning of the 21st century, the Economic Community of West African States (ECOWAS) has been ensuring respect for human rights. This shift in the mandate of ECOWAS was made possible by way of the revision of the substantive jurisdiction of its Court of Justice in 2005. The ECOWAS Court has since then courageously and actively adjudicated human rights matters. However, the jurisdiction of the Court raises some issues with respect to its legality. Looking at some of these issues, this study demonstrates that, despite the lack of any express provisions in the legal instruments, the relationship between human rights and the realisation of the ECOWAS objectives justifies the claim by the organisation to protect fundamental rights. Regarding the sui generis regime, which, absent its own bill of rights, relies on external norms (including the African Charter on Human and Peoples’ Rights) borrowed by the organization, it does not suffer from any illegality. Its regularity remains evidenced by the recourse to international law sources, in general, and particularly to sources of ECOWAS Community law, although the legal regime of these imported norms and standards remains unclear. Besides its well-grounded legality, the ECOWAS mechanism can, in addition, claim to be effective because of the communitarian nature of the anchoring system and the immediate jurisdiction the Court has claimed over cases of human rights violations.